Prospects of Bangladesh as a halal tourism destination - Md. Tariqul Islam (Journal of Halal Product and Research)
Halal tourism has opened a new horizon in the world tourism industry, both Muslim as well as many non-Muslim countries are showing their enthusiasm in Halal tourism. Bangladesh is the fourth largest Muslim populated country and the home of many Muslim architectures. Therefore, there is immense potential for Halal tourism in this country.  The objectives of this study are to analyze the prospects of Bangladesh as a destination of Halal Tourism by identifying the strengths, weaknesses, opportunities, and threats of Halal tourism in Bangladesh. To meet the objectives of this research both qualitative and quantitative method has been used. This study is a descriptive study and the majority of the data has been collected by the qualitative method from the existing literature and a survey of 93 people was conducted in the quantitative method. The result shows that Bangladesh is a promising country in the Halal tourism industry but it has some barriers too, which can be overcome by taking proper initiatives.